Effect of Fitohormones and Fertilizers on the Rooting and Growth of Mini-cuttings of Coffee (Coffea arabica) F1 hybrids - Matamoros Quesada, Andrey (2020)
[Introduction]: CATIE is seeking to optimize the horticultural technique of rooting coffee mini-cuttings for commercial multiplication of hybrids on a massive scale and at low cost. [Objective]: The objective of the study was to determine the effect of different fertilizers and hormonal stimulants on the rooting ability of cuttings and subsequent growth of the resulting plants. [Methodology]: Mini-cuttings of three coffee hybrids were used, treated with different combinations of a biostimulant, a rooting powder, a formula based on multiminerals, vitamins and phytohormones, and three fertilizers (NP, ZnP, hydroponic solution), and set to root in plastic tunnels with irrigation. Rooted plants were transplanted into bags for a 3-month nursery growth period. [Results]: The rooting phase concluded at 12 weeks, with a mean rooting percentage greater than 89 %, without differences between treatments or between hybrids. Significant differences were found between treatments for root length, with superiority of the combination of the rooting powder with the ZnP fertilizer. In the nursery phase, significant differences were found between treatments for plant height, fresh weight of aerial part, and fresh and dry root weight, highlighting in all cases the combinations of the rooting with the multimineral complex or with the ZnP fertilizer. The L12A28 hybrid stood out in almost all the variables evaluated. [Conclusions]: The study showed the importance of using auxinic and nutritional supplements during the rooting phase to optimize the performance of the plants in the nursery. Likewise, it showed the feasibility of the technique of rooting cuttings as a simple and efficient method for the multiplication of the hybrids.